Bugis dan Islam Persebaran Darud Dakwah Wal' Irsyad (DDI) di Indonesia - Andi Faisal Bakti (Buletin Al-Turas, 2006)
The development of Islamic Institution in South Sulawesi from Madrasah Arabiyah Islamiyah (MAI) in Sengkang until becomes Darud Dakwah wal 'Irsyad (DDI) is not far from a important role of civil society such as goverment, public figure, internal and external organization, and entrepeneur. Besides, it also involves ertain person like AGHM As'ad amd AGH Abdul Rahman Ambo Dalle.